2002
DOI: 10.1046/j.1469-8137.2002.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi respond to the substrate pH of their extraradical mycelium by altered growth and root colonization

Abstract: Summary• To test the response of arbuscular mycorrhizal (AM) fungi to a difference in soil pH, the extraradical mycelium of Scutellospora calospora or Glomus intraradices, in association with Plantago lanceolata, was exposed to two different pH treatments, while the root substrate pH was left unchanged.• Seedlings of P. lanceolata, colonized by one or other of the fungal symbionts, and nonmycorrhizal controls, were grown in mesh bags placed in pots containing pHbuffered sand (pH around 5 or 6). The systems wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(103 citation statements)
references
References 56 publications
9
91
2
1
Order By: Relevance
“…Arbuscular mycorrhizal fungi, although obligate plant symbionts, have extensive extra-radical mycelial networks that spread throughout the soil and it is likely that the effect of soil pH on mycelia produces strong selective pressures structuring AM fungal niche space (van Aarle et al, 2002). However, previous studies on soils with a smaller range of pH have suggested that host plant species is an important factor structuring AM fungal communities (Helgason et al, 2007).…”
Section: Environmental Niche Of Am Fungimentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi, although obligate plant symbionts, have extensive extra-radical mycelial networks that spread throughout the soil and it is likely that the effect of soil pH on mycelia produces strong selective pressures structuring AM fungal niche space (van Aarle et al, 2002). However, previous studies on soils with a smaller range of pH have suggested that host plant species is an important factor structuring AM fungal communities (Helgason et al, 2007).…”
Section: Environmental Niche Of Am Fungimentioning
confidence: 99%
“…LINGFEI et al (2005) found results similar to ours, where soil pH was found to be correlated with the extent of hyphal and arbuscular colonization in grasses. Colonization and extraradial mycelium formation by AMF are known to be altered by soil pH ( VAN AARLE et al 2002). COUGHLAN et al (2000) inferred that the tendency for colonization levels to increase with pH was due to the stimulation of the additional AMF taxa and/or a greater ability of the taxa present to colonize host roots.…”
Section: Discussionmentioning
confidence: 99%
“…1). This decrease in the fungus colonization under salt stress may be due to a reduced germination of fungal spores (Van Aarle et al 2002, Al-Khaliel 2010.…”
Section: Discussionmentioning
confidence: 99%